Pembelajaran Tahfiz Al-Qur’an di UPTD SMPN 1 Kecamatan Gunuang Omeh Kabupaten Lima Puluh Kota - Dila Novita Sari; Wedra Aprison; Zulfani Sesmiarni; Pendi Hasibuan (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of this research is the non-achievement of the target of memorizing the Qur'an which has been set by the UPTD SMPN 1 Subdistrict of Gunuang Omeh, Lima Puluh Kota Regency. The purpose of this study is to determine the factors that influence why students do not achieve the memorization targets that have been set in the study using a descriptive qualitative approach, using key informants are students and tutors in Tahfiz learning and supporting informants are religious teachers and teachers in UPTD SMPN 1 Gunuang Omeh District, Fifty Cities District. Data collection by observation and interview methods. Data analysis techniques with data reduction, data display and data verification. To test the validity of the data by using source triangulation. The results of this study are there are several factors why students at UPTD SMPN 1 Gunuang Omeh District do not reach the memorization target, there are 2 factors, namely internal and external factors. Internal factors: students' interest and motivation in memorizing the Qur'an are lacking, students are less focused on memorizing letters, students are lazy in repeating memorization either at school or at home, many activities that make students do not have time to memorize. External factors are the letter that will be memorized according to students is difficult or the last verse is long, friends have a great influence on students' motivation and interest in memorizing because friends have a bad influence, mentor teachers in learning Tahfiz Al-Qur'an also affect student memorization, punishments and prizes have not been implemented in schools, the environment is not supportive in the learning process of Tahfiz Al-Qur'an and the allocation of time is not enough for learning Tahfiz Al-Qur'an. Keywords: Learning, Tahfiz Al-Quran Learning, Tahfiz Al-Quran